Comparative Analysis of Understorey Floristic Diversity and Carbon Stocks in Poorly and Intensively Managed Tectona grandis Plantations - A. Asare; W. A. Asante; N. Owusu-Prempeh; E. Opuni Frimpong; D. Adusu (International Journal of Forestry Research)
The role of forest plantations in carbon sequestration and biodiversity conservation is a topical issue among researchers and policymakers globally. This study compares understorey floristic diversity and carbon stock of a 15-year-old monoculture Tectona grandis plantation under intensive and poor management in a dry semideciduous ecological zone of Ghana. The study employed a nested plot design with twelve (12) 50 m × 50 m plots laid at 50 m intervals along a diagonal line transect on both study sites for the sampling of Tectona grandis trees. Understorey trees, shrubs, and climbers were sampled within 10 m × 10 m subplot, whilst grasses and herbs were sampled within 1 m × 1 m quadrats. The study revealed a significantly higher understorey species diversity in the intensively managed plantation (Shannon index; species richness) compared with that of the poorly managed plantation. Similarly, total biomass (189.80 ± 1.846 Mg/ha) and carbon stock (94.90 ± 0.92 Mg C/ha) in the intensively managed plantation were observed to be significantly higher than the poorly managed plantation (biomass: 138.54 ± 3.70 Mg/ha; carbon stock: 64.27 ± 1.85 Mg C/ha), whiles the species composition between the two sites was different (Sorenson’s similarity index: 0.47). The study, therefore, concludes that silvicultural forest management interventions improve the understorey floristic diversity and carbon stock in monoculture plantations. Consequently, the study recommends the adoption of silvicultural interventions in plantation management in Ghana to improve their contributions to carbon sequestration and floristic diversity conservation.